Public perception of healthcare system response to COVID-19: Findings from a web based observational study in Villavicencio, Colombia - César García Balaguera; Olga Yesenia García; María Victoria Gutiérrez (Public Library of Science (PLoS), 2022)
This study explores the community perceptions of COVID-19 and the healthcare system's response to it.: A web-based descriptive observational study was conducted on the general population during the third quarter of 2020 through the application of a survey via social media. Of the sample, 55% have minimal connection with prevention programs, while 66.3% received little or no information about COVID-19, and 69.62% were considered at risk of getting sick from COVID-19. Further, 73.14% were afraid to go to healthcare centers fearing the risk of becoming infected by COVID-19. The low-income population is at greater risk (OR 4.32), as well as those who have not been informed by their insurer of the risks of COVID-19 (OR 2.18). There is a need to strengthen the healthcare system and the quality and design of effective self-care educational interventions during the pandemic.